Transformation of protoplasted yeast cells is directly associated with cell fusion. - Harashima, S (1984)
The frequency of cell fusion during transformation of yeast protoplasts with various yeast plasmids with a chromosome replicon (YRp or YCp) or 2 mu DNA (YEp) was estimated by two methods. In one method, a mixture of protoplasts of two haploid strains with identical mating type and complementary auxotrophic nuclear markers with or without cytoplasmic markers was transformed. When the number of various phenotypic classes of transformants for the nuclear markers was analyzed by equations derived from binominal distribution theory, the frequency of nuclear fusion among the transformants was 42 to 100% in transformations with the YRp or YCp plasmids and 28 to 39% with the YEp plasmids. In another method, a haploid bearing the sir mutation, which allows a diploid (or polyploid) homozygous for the MAT (mating type) locus to sporulate by the expression of the silent mating-type loci HML and HMR, was transformed with the plasmids. Sporulation ability was found in 43 to 95% of the transformants with the YRp or YCp plasmids, and 26 to 31% of the YEp transformants. When cytoplasmic mixing was included with the nuclear fusion, 96 to 100% of the transformants were found to be cell fusants. Based upon these observations, we concluded that transformation of yeast protoplasts is directly associated with cell fusion.